Infecção pelo Schistosoma Mansoni em estudantes como indicador da infecção na população em área rural de alta prevalência - Kellen Rosa Coelho (2010)
Objective: this epidemiological, cross-sectional and analytical study aimed to analyze the infection by S. mansoni in students as an indicator of infection in the population of three rural endemic areas for schistosomiasis in the Jequitinhonha Valley, Min